Fear of the Dark: Surrealist Shadows in The Nigger of the "Narcissus" - Lawtoo, Nidesh (Modern fiction studies, 2014)
This article argues that in The Nigger of the ‘Narcissus’ Joseph Conrad gives narrative form to a poetics of darkness that anticipates surrealist concerns with self-dissolution, mimeticism, and loss of identity. Aligning Conrad with Roger Caillois's surrealist account of mimesis, the author argues that Conrad strives to "make [us] see" a fear of the dark that has psychological, philosophical, and narratological implications. This essay furthers a mimetic line of inquiry in modernist studies and argues that Conrad's images of darkness cast shadows that are neither realistic nor impressionistic, but surrealistic instead.